State-of-the-Art Drought Handling in Indonesia - Nurlambang, Triarko; Dimyati, Ratih Dewanti; Purbantoro, Babag; Rahatiningtyas, Nurul Sri; Legowo, Dewanti Aisyah; Fakhruddin, Ahmad; Dimyati, Muhammad; Enshito, Grizzly Pradipta Singhasana (Faculty of Geography, Universitas Gadjah Mada, 2024)
Droughts tend to become more extreme, longer, and more frequent as an impact of climate change. Droughts now impact various development activities, especially those reliant on water resources, like agriculture for food security. Drought management issues in Indonesia stem from inadequate regulations and laws regarding drought response, due to intricate agency procedures and overlapping responsibilities. Nevertheless, there are currently established partial regulations and laws that govern the management of meteorological data and the accessibility of water resources. Without clear rules, policies, and frameworks, government policies on drought become less effective and overlapping. The research and novelty aim to design an integrated framework for handling drought by examining the present circumstances of relevant agencies using spatial nexus framework that is divided into three stages (construction, deconstruction, and reconstruction). During the first stage, the focus goes toward developing the construction framework will be proposed. The construction framework was conducted descriptively through a desk research method of drought management public policies, institutions, and operating systems for the agricultural sector in Indonesia. Moreover, a panel discussion was held to obtain the data and information about drought management by the government. Field observations were conducted to determine the handling of water resources practically for agriculture. Thus, drought management has been more concentrated on meteorological/climatological and hydrological elements. Moreover, it focuses on the statistical results of public and agricultural activities rather than on their socioeconomic consequences. A spatial approach will become the integration node of meteorological/hydrological elements, socioeconomic components, and agricultural activities.